Low-Level Stimulation and Ethanol Ablation of the Vein of Marshall Prevent the Vagal-Mediated AF - Liu, Fei; Sun, Wei; Li, Yan; Sun, Yuanjun; Yu, Xiaohong; Yin, Xiaomeng; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2021)
Background: The mechanisms for the vein of Marshall (VOM) mediated atrial fibrillation (AF) are not completely understood. We sought to evaluate the contribution of the intrinsic cardiac autonomic nervous system in VOM mediated AF. Method: Seven mongrel dogs were administered propranolol and continuously exposed to left superior ganglionated plexi (LSGP) stimulation, LSGP + low-level VOM stimulation, LSGP + atropine administration, LSGP + VOM filling with ethanol separately. The effective refractory period (ERP) and window of vulnerability (WOV) at the left superior pulmonary vein (LSPV), left inferior pulmonary vein (LIPV) and left atrial appendage (LAA) were measured. LSGP stimulation significantly shortens the ERP and prolonged the ERP dispersion and WOV in LSPV, LIPV, and LAA. Interestingly, low-level VOM stimulation, atropine administration, or VOM filling with ethanol were able to attenuate the effects of LSGP in all sites. Conclusion: VOM as an inter-communication pathway of ganglionated plexis plays an important role in the development of vagal-related AF.